The potential human health hazard of nitrates in drinking water: a media discourse analysis in a high-income country - Leah Grout; Tim Chambers; Simon Hales; Marnie Prickett; Michael G. Baker; Nick Wilson (Environmental Health, 2023)
Abstract Background Recent studies linking low levels of nitrate in drinking water to colorectal cancer have raised public concerns over nitrate contamination. The aim of this study was to analyze the media discourse on the potential human health hazard of nitrates in drinking water in a high-income country with a large livestock industry: New Zealand (NZ). Methods Searches of media sources (“major newspapers”) held by the Factiva database for the NZ setting in the five-year period 17 December 2016 to 20 December 2021. Results The largest number of media items was observed for 2017 (n = 108), the year of a NZ general election, with a notable decrease in 2020 (n = 20) that was likely due to the Covid-19 pandemic, which dominated health media. However, the percentage of these media items with a health focus steadily increased over time, from 11.1% of all articles in 2017 to 51.2% in 2021. The most commonly mentioned health hazard was colorectal cancer, followed by methemoglobinemia. The temporal pattern of media items suggests that the release of scientific studies and scholarly blogs was associated with the publication of subsequent media items. Major stakeholders involved in the discourse included representatives of local and central government, environmental and recreational interest groups, researchers, local residents, agricultural interest groups, and health organizations. Māori (Indigenous New Zealanders) values or perspectives were rarely mentioned. Conclusions Analysis of major newspapers for a five-year period indicated that a wide range of expert comment and opinions were made available to the public and policy makers on the issue of nitrates in water. While many different stakeholder views were captured in the media discourse, there is scope for the media to better report the views of Māori on this topic. There is also a need for articles detailing the health issues to also refer to the environmental, recreational, and cultural aspects of protecting water quality to ensure that the public, policy makers, and regulators are aware of co-benefits.